EXPLORING THE MEANING OF ORGANIZATIONAL CULTURE: A QUALITATIVE STUDY OF THE DYNAMICS OF VALUES AND PRACTICES AT KAYUHAN COFFEE - Yosua Putra Marsando; Iing Sri Hardiningrum (SOSIOEDUKASI, 2025)
This research aims to explore the meaning of organizational culture formed at Kayuhan Coffee, a mobile coffee business operating on the roadside. Using a qualitative approach and case study method, this research explores the values, symbols, and work practices that shape organizational culture at Kayuhan Coffee. Data were collected through in-depth interviews, participatory observation, and field documentation. The findings uncover the fact that the organizational culture at Kayuhan Coffee is built on family values, entrepreneurial spirit, and openness in service. Practices such as warm interactions with customers, operational flexibility, and the use of open spaces as social facilities also strengthen the unique character of an adaptive and inclusive organizational culture. This research adds to the knowledge of how organizational culture can be formed and developed in the context of non-conventional small businesses such as mobile coffee, as well as opening space for further studies on the dynamics of informal work culture in the creative economy sector.